Perivascular Innervation in the Nasal Mucosa and Clinical Findings in Patients with Allergic Rhinitis and Idiopathic Rhinitis - Carvalho, Thiago; Mello Jr, João Ferreira de; Caldini, Elia Tamaso Espin Garcia; Salgado, Daniel Calduro; Carvalho, Nicole Mary Garcia de; Damaceno-Rodrigues, Nilsa Regina; Voegels, Richard Louis (International Archives of Otorhinolaryngology, 2023)
Introduction The nonspecific hyperreactivity of rhinitis has been attributed to neurotrophins activating sensory nerves and inflammatory cells. The relationship between these markers and the intensity of the symptoms is not well established and few studies have evaluated individuals with idiopathic rhinitis.Objective The present study aims to evaluate whether perivascular innervation and nerve growth factor (NGF) are related to the intensity of the clinical conditions in allergic rhinitis (AR) and idiopathic rhinitis (IR).Methods A total of 15 patients with AR and 15 patients with IR with the indication for inferior turbinectomy (associated or not with septoplasty) were selected. The patients received a score according to their signs and symptoms. After the surgery, we quantified eosinophils, mast cells, NGF, and nerve fibers in the nasal turbinate.Results The score of the signs and symptoms was higher in the AR group. Nerve growth factor was found in the cytoplasm of inflammatory cells in the submucosa in greater quantity in the AR group. The nerve fibers were distributed throughout the tissue, mainly in the subepithelial, glandular, and vascular regions, and there was no difference between the groups. Greater perivascular innervation was associated with a higher signs and symptoms score.Conclusions We concluded that these findings suggest that the NGF produced by submucosal inflammatory cells stimulates increased perivascular innervation in rhinitis, thus directly reflecting in more intense clinical conditions, especially in AR.
Keywords: allergic rhinitis; hyperreactivity; innervation; nerve growth factor; neurotrophins